ANALISIS FLUIDA DAN PEMANFAATAN MATA AIR PANAS DAERAH SULILI KABUPATEN PINRANG PROVINSI SULAWESI-SELATAN - Umar, Emi Prasetyawati; Nawir, Alfian; Husain, Jamal Rauf; Tamar, Khadijah Rezkiani; Maria, Maria; Jamaluddin, Jamaluddin; Wakila, Muhamad Hardin (Jurnal Geosaintek, 2025)
The research area shows that geothermal manifestations are in the form of hot springs, and analysis of the hot water springs fluid is very important for more utilization. The aim of this study is to analyze the physical property of the hot water springs, hot spring fluid conditions, to find out the benefit of the hot water springs in the research areas. The method used is the analysis of physical properties of value of pH, smell, taste, temperature, colour, H2S as sulfide, TDS (Total Dissolved Solid) and DHL (Electrical Conductivity). The results showed that the characteristic of the hot water springs are shows the colored water of Sulili nodes with the results from laboratory analysis get 4-23 TCU, sulfur-smelling, taste brackish, surface temperature of 45°C-57ºC, pH relatively neutral-alkaline (7.8-7.9), 1.85-2.13g/L TDS shows springs the heat belongs to brackish water and non karbonat hardness water, the turbidity of 0.95-6.04 NTU and DHL i.e. 4.23-4.52 mS/cm. The average pH value of hot springs is that it has a neutral-alkaline pH, identifier i.e. hot spring low temperature water which is dominated by water. The benefits of hot springs the area of research in the field of tourism as a place of hot water bath, health and as a field studies centre.